Orientalism from a Postcolonial Perspective in the Novel Saffron Dreams by Shaila Abdullah - Azzahra, Nabila; Ilmi, Najihatul; Alhadi, Muhammad Wahda (Litteratura: Jurnal Bahasa dan Sastra, 2024)
Saffron Dreams, written by Shaila Abdullah, is an intriguing work of fiction that tells the story of the harsh life of a Muslim woman from the East in America after the 9/11 tragedy. The double standards applied by America are not only limited to views of Muslims but extend to Eastern cultures as a whole. It is here that the Western perspective of the East, known as Orientalism, is portrayed as though the West is superior to the East. This study examines how American Orientalism and Postcolonialism influence and shape the identity dynamics of Arissa Illahi. This research employs a descriptive and qualitative method, using Edward Said's theory of Orientalism. The findings show that Arissa experiences various dynamics related to her identity, which is based on Islamic-Pakistani culture. Orientalism, within the context of American Postcolonialism, disturbs her identity as a Pakistani Muslim, leading to a series of crises and efforts at adaptation full of uncertainty. Arissa's character plays a crucial role as a representation of Muslim women, depicting the struggle of Eastern Muslim women fighting for their rights as human beings. Her struggle serves as a means of confronting Western Orientalist views, demonstrating solidarity with Muslim women from third-world countries living in America.